2020
DOI: 10.1038/s41438-020-00422-w
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome-scale reference genome of Lobularia maritima, an ornamental plant with high stress tolerance

Abstract: Lobularia maritima (L.) Desv. is an ornamental plant cultivated across the world. It belongs to the family Brassicaceae and can tolerate dry, poor and contaminated habitats. Here, we present a chromosome-scale, high-quality genome assembly of L. maritima based on integrated approaches combining Illumina short reads and Hi–C chromosome conformation data. The genome was assembled into 12 pseudochromosomes with a 197.70 Mb length, and it includes 25,813 protein-coding genes. Approximately 41.94% of the genome con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 104 publications
(121 reference statements)
1
9
0
Order By: Relevance
“…Recent studies have shown that L. maritima genome is ~197.70 Mb in size, with 88.31% (174.59 Mb) of the sequences assigned to 12 pseudochromosomes [ 9 ]. The L. maritima genome is smaller than that of other Brassicaceae species; it contains 25,813 genes and large numbers of repetitive elements [ 9 ].…”
Section: Salt Tolerance In Halophytesmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have shown that L. maritima genome is ~197.70 Mb in size, with 88.31% (174.59 Mb) of the sequences assigned to 12 pseudochromosomes [ 9 ]. The L. maritima genome is smaller than that of other Brassicaceae species; it contains 25,813 genes and large numbers of repetitive elements [ 9 ].…”
Section: Salt Tolerance In Halophytesmentioning
confidence: 99%
“…Recent studies have shown that L. maritima genome is ~197.70 Mb in size, with 88.31% (174.59 Mb) of the sequences assigned to 12 pseudochromosomes [ 9 ]. The L. maritima genome is smaller than that of other Brassicaceae species; it contains 25,813 genes and large numbers of repetitive elements [ 9 ]. The adaptive divergence of a species from closely related species is frequently linked to gene families with significantly enlarged or contracted copy numbers [ 43 ].…”
Section: Salt Tolerance In Halophytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the pioneering studies demonstrating the paleotetraploidy of the Arabidopsis genome and the mesohexaploidy of the “diploid” Brassica and Brassiceae species (The Arabidopsis Genome Initiative, 2000; Lysak et al, 2005; Parkin et al, 2005), many other clade‐ or genus‐specific mesopolyploid events have been discovered in Brassicaceae (e.g., Mandáková et al, 2010, 2017a; Kagale et al, 2014; Geiser et al, 2016; Huang et al, 2020; Guo et al, 2021). Mesopolyploid genomes have diploidized genomes with low chromosome number and often biased subgenome fractionation.…”
Section: Figurementioning
confidence: 99%